The Effect of the TBLA Method on Strengthening Teacher’s QoP as a Contribution to Student Character Development - Ni Ketut Suarni; I Wayan Susanta; I Ketut Dharsana; Wayan Eka Paramartha; Gede Nugraha Sudarsana; Ulan Sari (Universitas Muhammadiyah Semarang, 2021)
Abstract— This study aims to determine the influence of Transcript Based Lesson Analysis (TBLA) methods on the priority level of the Quality of Pedagogical (QoP) elements in student character development. This type of research is experimental research with a post-test control group design research design. This research sample was elementary school students in Cluster XI of Buleleng Subdistrict who were selected using random sampling techniques. Research data collection instruments are using rubrics. The data analysis method used is bivariate statistical analysis whose data source is obtained from transcript-based lesson analysis. The results showed that 1) the priority level of the teacher's QoP element of 80% was obtained in Pedagogy Content Knowledge; 2) the priority level of the student character behavior element of 72% is obtained in the nationalist and mutual cooperation categories; 3) Methods and insights contribute to the character development of students by 89%. Keywords—TBLA, QoP, student character